„Kormányablakok a kirakatban” Az integrált ügyintézési pontok hazai fejlődésének legfontosabb állomásai - Jakab, Viktória (Debreceni Jogi Műhely, 2016)
The ever-increasing pace of development, experienced in all aspects of life, has become a major factor of our times. Public administration is no exception to this tendency. I have chosen the government windows (and other miscellaneous administrative bodies operating alongside them) established in the past five years as the topic of my study exactly because of this – their development is expected to remain unbroken in the future as well. During my research, I paid special attention to past and current legal changes, aiming to provide a comprehensive view on the establishment, operation, and evolution of the integrated administration points in Hungary. My study also covers the current state and the expected developments of domestic e-Administration solutions. Finally, I also offer some conclusions and recommendations regarding the large-scale deployment of the planned single-window administrative system.